Frequency of Depression among Patients with Chronic Liver Disease - Aziz, Zainab; Kareem, Owais (Biological and Clinical Sciences Research Journal, 2025)
Depression is a frequent but under-recognised comorbidity in patients with chronic liver disease and is associated with poorer treatment adherence, impaired quality of life, and adverse clinical outcomes. Data from Pakistan remains limited, particularly from tertiary care settings in South Punjab. Objective: To determine the frequency of depression among patients with chronic liver disease and to examine its association with selected sociodemographic and clinical factors. Methods: This descriptive cross-sectional study was conducted at the Department of Psychiatry, Nishtar Hospital, Multan, over the six months from May 2024 to October 2024. A total of 170 patients aged 20–45 years with a documented diagnosis of chronic liver disease for at least two years were enrolled using non-probability convenience sampling. Depression was assessed using the depression subscale of the Hospital Anxiety and Depression Scale, with a score > 8 indicating depression. Sociodemographic and clinical variables were recorded using a structured proforma. Data were analysed using SPSS version 23. Frequencies and percentages were calculated for categorical variables, and means ± standard deviations were calculated for continuous variables. Post-stratification chi-square tests were applied, with p ≤ 0.05 considered statistically significant. Results: The mean age of participants was 34.1 ± 6.2 years, and 56.5% were male. Depression was identified in 63 patients, yielding a frequency of 37.1%. Higher frequencies of depression were observed among females, rural residents, unemployed participants, obese individuals, those with lower educational status, and patients with a longer duration of chronic liver disease. Statistically significant associations were noted for gender, area of residence, employment status, obesity, education level, and duration of chronic liver disease (p < 0.05 for all). Conclusion: More than one-third of patients with chronic liver disease in this tertiary care setting had comorbid depression, with a higher burden among socially and clinically vulnerable subgroups. Routine screening for depression should be integrated into chronic liver disease care pathways to support comprehensive management and improve patient-centred outcomes.